Comparative Antioxidant Activity on The Ficus benjamina and Annona reticulata Leaves - Nyi Mekar Saptarini; Irma Erika Herawati (Intelektual Pustaka Media Utama, 2015)
Antioxidants can prevent free radical formation. Natural antioxidants found in many plants, such as Ficus benjamina and Annona reticulata. The study aimed to compare the antioxidant activity of extracts and fractions of Ficus benjamina and Annona reticulata leaves against 1,1-diphenyl-2-picrilhydrazyl. The steps of this study consist of extraction, fractionation with n-hexane, ethyl acetate and water, phytochemical screening, antioxidant activity determination, and comparing the IC50 values. Percentage scavenging activity of the extracts and fractions against DPPH was calculated to determine the antioxidant activity. The IC50 value of Ficus benjamina was 127.86 ppm for ethanolic extract, 94.01 ppm for water fraction, 115.48 ppm for ethyl acetate fraction, and 335.50 ppm for n-hexane fraction. The IC50 value of Annona reticulata was 274.31 ppm for ethanolic extract, 211.42 ppm for water fraction, 367.91 ppm for ethyl acetate fraction, and 741.08 ppm for n-hexane fraction. The results showed that the Ficus benjamina water fraction was the best antioxidant compared to other extract and fraction.